Evaluation of variable-rate spray application on tree crop - Silva, João Eduardo Ribeiro da (2017)
On tree crops, a great diversity of canopy structure and density is found. Using conventional sprayers, much of the sprayed material is wasted. The variability of the tree canopies is most of the times not taken into consideration, generating conditions of underspray, overspray and drift. Tree Row Volume (TRV) methods have been developed to indirect measure the canopy and adjust the sprayed volume to the plants characteristics. However, the constant rate application does not eliminate overspray and underspray, as well as application between trees, which could lead to spray drift. The use of sensors for tree crops canopy characterization together with variable-rate spray application can produce efficient spray deposition and coverage on tree crops, and reduce the drift. However, variable-rate sprayers modulate the number of operating nozzles and the duty cycle constantly, causing an effect on the system pressure. A variable-rate intelligent sprayer implementing a high speed laser scanner was developed for tree crops customized spraying. It had 40 nozzles on total, with the nozzles being independently capable of spraying at 10 percentages of the maximum flow rate (duty cycle). The nozzle output was adjusted by solenoid valves. Experiments were conducted to further evaluate the performance under field conditions of the variable-rate intelligent sprayer and a conventional constant-rate sprayer, studying the spray drift, spray coverage and deposition inside Ash tree canopies. A second role of tests was realized to evaluate the pressure behavior and its effect on flow rate of the intelligent sprayer on several combinations of duty cycle and number of operating nozzles. The flow rate was measured for the different combinations and the pressure was checked. The deposition test was at factorial scheme 2 x 3 (two sprayers and three travel speeds), with three replications in blocks randomized. The drift test was at factorial scheme 2 x 3 x 5 (two sprayers, three travel speeds and, five distances of drift collectors, in split-plot), with three replications in blocks randomized. For these tests it was used the tracer Brilliant Sulphoflavine (BSF) at 2.0 g L-1 concentration. The first test for evaluation of the intelligent sprayer’s flow-rate and pressure behavior was at factorial scheme 10 x 40 (10 duty cycles and 1-40 operating nozzles), being the sprayer’s pressure set to 50 PSI (344.7 kPa) at the beginning of the test (varied pressure condition). The second test on the intelligent sprayer was at factorial scheme 10 x 5 (10 duty cycles and 1, 10, 20, 30 or 40 operating nozzles), with the pressure staying constant at 35 PSI (241 kPa) (constant pressure condition). The use of sensors together with variable- rate delivery systems, implementing mostly solenoid valves to control spray application, have proportionated pesticide savings and drift reduction. The variable-rate intelligent sprayer reduced the application rate in 64%, drift to the air in 92-94% and drift to the ground in 58-98%. Spray coverage and deposition were similar for both sprayers and not affected by sprayers travel speed. It was observed more accentuated pressure decay on the varied pressure condition. The flow rate of the variable-rate intelligent sprayer could be described through a polynomial regression curve, for both varied and constant pressure conditions.